Reproductive Success of the Creamy-Bellied Thrush in a Southern Temperate Zone - Astié, Andrea Alejandra (2012)
We describe the breeding biology and reproductive success of a Creamy-bellied Thrush (Turdus amaurochalinus) population from a southern temperate zone in western Argentina. We found 236 Creamy-bellied Thrush nests of which most were predated (67%). The breeding season was from late October to late December and clutch size was three eggs. Egg survival, hatching success, and fledgling survival of non-depredated nests were quite high (0.67 6 0.03, 0.74 6 0.03, and 0.87 6 0.04, respectively). The number of eggs in the nest did not affect egg survival or hatching success, but number of nestlings in the nest affected fledgling success. Daily nest mortality was higher during the early and late nestling period than during laying, and early and late incubation periods. Highest nest mortality coincided with periods when activity of parents at the nest was highest. The clutch size was similar to data reported for thrushes from the tropics and south temperate areas, and lower than reported for thrushes from north temperate areas. This latitudinal pattern is similar to the general pattern described for passerines in the tropics and southern temperate areas.